(untitled) (Global Journal of Computer Science and Technology, 2014)
Abstract- In mobile ad-hoc networks (MANETs), providing quality of service is more challenging than wired networks, because of multi hop communication, node connectivity and lack of central co-ordination. Mobile ad-hoc networks need sure distinctive characteristics which might cause difficulties providing QoS in such network. Coming up with of multi constrained QoS routing protocols remains troublesome. As a result of routing protocols must satisfy the numerous QoS metrics at a time. Genetic algorithm based routing protocol will give the solution for multi constrained QoS routing problem. In existing genetic algorithm based routing, achieving energy efficiency is the major drawback. To overcome this drawback, in this paper, we have proposed genetic algorithm based energy efficient QoS routing for MANET. Proposed GA based routing algorithm discovered the shortest path from source to destination, which can consumes less energy compare to existing algorithms. In this paper TCP,CBR and video sources are applied at a time then energy consumption of proposed algorithm is compared with existing normal GA based and AOMDV. Simulation results show that proposed algorithm consumes less energy towards given scenario. Simulations are performed in NS-2.